2018
DOI: 10.1155/2018/2475047
|View full text |Cite
|
Sign up to set email alerts
|

NRF2 Activation Inhibits Both TGF‐β1‐ and IL‐13‐Mediated Periostin Expression in Fibroblasts: Benefit of Cinnamaldehyde for Antifibrotic Treatment

Abstract: Systemic fibrosing or sclerotic disorders are life-threatening, but only very limited treatment modalities are available for them. In recent years, periostin (POSTN), a major extracellular matrix component, was established by several studies as a novel key player in the progression of systemic fibrotic disease. In this research, we revealed the involvement of oxidative stress in the expression of POSTN induced by TGF-β1 and IL-13 in dermal fibroblasts. We found that the antioxidant cinnamaldehyde activated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 57 publications
0
33
0
Order By: Relevance
“…IL-4-and IL-13-mediated activation of STAT6 could feasibly upregulate IL-24 production [140,141]. IL-13-induced STAT6 activation upregulates the production of periostin, which promotes allergic inflammation and fibrosis in keratinocytes [142,143]. Periostin stimulates keratinocytes to produce IL-24 [144,145].…”
Section: Downregulation Of Ivl Lor and Flg By Il-4/il-13mentioning
confidence: 99%
“…IL-4-and IL-13-mediated activation of STAT6 could feasibly upregulate IL-24 production [140,141]. IL-13-induced STAT6 activation upregulates the production of periostin, which promotes allergic inflammation and fibrosis in keratinocytes [142,143]. Periostin stimulates keratinocytes to produce IL-24 [144,145].…”
Section: Downregulation Of Ivl Lor and Flg By Il-4/il-13mentioning
confidence: 99%
“…Another important function of IL-13 is its profibrotic effect which is believed to link to fibrotic process or remodeling in chronic atopic inflammation. [128][129][130][131][132] Fichtner-Feigl et al 132 have demonstrated that the ligation of IL-13Ra2 by IL-13 induces the production of transforming growth factor-b and facilitates fibrosis. Furthermore, chitinase 3-like 1 (CHI3L1), also known as breast regression protein 39 in mice and YKL-40 in humans, is known to bind IL-13Ra2.…”
Section: Il-13ra2 and Scratch Injurymentioning
confidence: 99%
“…It plays its antioxidant role by binding to DNA antioxidant response element (ARE) and the Nrf2-ARE pathway has an important protective effect in ischemia-reperfusion injury (15). Nrf2 suppresses IL-13 and IL-22 secretion (16,17). IL-13 and IL-22, upregulate the STAT3 pathway and cause in ammation (18,19).…”
Section: Discussionmentioning
confidence: 99%